Discovering a Four-Gene Prognostic Model Based on Single-Cell Data and Gene Expression Data of Pancreatic Adenocarcinoma - Huang, Weizhen; Li, Jun; Zhou, Siwei; Li, Yi; Yuan, Xia (Frontiers in Endocrinology, 2022)
Background: Pancreatic cancer has a 5-year overall survival lower than 8%. Pancreatic adenocarcinoma (PAAD) is the most common type. This study attempted to explore novel molecular subtypes and a prognostic model through analyzing tumor microenvironment (TME). Materials and Methods: Single-cell RNA sequencing (scRNA-seq) data and expression profiles from public databases were downloaded. Three PAAD samples with single-cell data and 566 samples with gene expression data were included. Seurat was used to identify cell subsets. SVA merged and removed batch effects from multichip data sets. Ciberport was used to evaluate the components of different cells in transcriptome, Consusclusterplus was used to identify molecular subtypes, and GSEA was used for functional enrichment analysis. Lasso-cox was performed to construct dimensionality reduction and prognosis model. Results: Memory B cells (MBCs) were identified to be significantly with PAAD prognosis. Two immune subtypes (IS1 and IS2) with distinct overall survival were constructed. 41 DEGs were identified between IS1 and IS2. Four prognostic genes (ANLN, ARNTL2, SERPINB5 and DKK1) were screened to develop a prognostic model. The model was effective in classifying samples into high-risk and low-risk groups with distinct prognosis. Three subgroups of MBCs were identified, where MBC_0 and MBC_1 were differentially distributed between IS1 and IS2, high-risk and low-risk groups. Conclusions: MBCs were closely involved in PAAD progression, especially MBC_0 and MBC_1 subgroup. The 4-gene prognostic model was predictive of overall survival and could guide immunotherapy for PAAD patients.